Sosialisasi Digital dan Pondok Belajar: Langkah Nyata Mewujudkan Desa Cerdas - Azizah Raudhatul Jannah; Elsya Erlandah; Lovia Phica Yola Emilza; Rafika Hayati; Ronna Uli Sitanggang (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2026)
The rapid development of digital technology has significantly transformed social interaction and learning processes in rural communities. Uncontrolled smartphone usage has led to low digital literacy and heightened risks of social media misuse among children and adolescents. This community service program, through the Community Service Program (KKN), aimed to improve digital literacy and establish a Learning Center (Pondok Belajar) as an educational space within the village. The methods included observation, socialization, digital literacy training, and academic mentoring for children. The results demonstrated an increase in community awareness regarding the responsible use of smartphones and enhanced learning motivation among children through the Learning Center activities. This program illustrates that the synergy between digital education and learning support can be a concrete step toward building a smart and competitive village in the digital era. The initiative highlights the importance of combining technology education with community-based programs to foster a more informed and empowered population in rural areas.